Experiencing parenthood, care and spaces of hospitality. Issue 2 (23rd July 2015) - Lugosi, Peter; Robinson, Richard N.S.; Golubovskaya, Maria; Foley, Laura; Harwell, Jan
Abstract: Drawing on research conducted in Australia and the United Kingdom, this paper explores how parenting and care provision is entangled with, and thus produced through, consumption in hospitality venues. We examine how the socio‐material practices of hospitality provision shape the enactment of parenting, alongside the way child‐parent/consumer‐provider interactions impact upon experiences of hospitality spaces. We argue that venues provide contexts for care provision, acting as spaces of sociality, informing children's socialization and offering temporary relief from the work of parenting. However, the data also highlight various practices of exclusion and multiple forms of emotional and physical labour required from care‐providers. The data illustrate children's ability to exercise power and the ways in which parents'/carers' experiences of hospitality spaces are shaped by their enactment of discourses of 'good parenting'. Finally, we consider parents'/carers' coping behaviours as they manage social and psychological risks associated with consumption in such public spaces of leisure.